Avaliação da qualidade de vida dos adolescentes em tratamento oncológico no Hospital das Clínicas da Universidade Federal de Minas Gerais - Karla Emilia de Sa Rodrigues (2011)
Few studies have been performed during childrens and adolescents cancer treatment to evaluate its interference on health related quality of life (HRQL). The purposes of this study were to evaluate the adolescents HRQL during cancer treatment at the Hospital das Clínicas of the Federal University of Minas Gerais from October 2007 to July 2010, the correlation of the HRQL scores among patients, family and doctors, and the correlation of HRQL scores with social demographic characteristics(age, gender and socioeconomic status) and type of neoplasia. A generic HRQL instrument was utilized, the Health Utilities Index (HUI). Forty-five patients and their respective family and doctor were asked to answer the questionnaire one month after diagnosis and beginning of treatment (T1) and then four or six months later for patients with solid tumors or with leukemia/lymphoma, respectively (T2). Nonparametric tests were used to compare T1 and T2 scores; Spearmans coefficient was used to test score correlation derived from patients, their families, and physicians. Patients median age was 14 years. Acute leukemia (40%) and lymphoma (26.7%) were the most frequent diagnosis. Forty-four patients received only chemotherapy as treatment and the others acombination of chemo and surgery and/or radiotherapy. On patients, families and doctors evaluation pain scores significantly decreased from T1 to T2. There was no statistical association of HRQL scores with social demographic characteristics (gender, age, family income, schooling of family members, or number of people at patientshome), type of neoplasia or treatment modalities. A high correlation between patients and family HRQL scores was observed both at T1 and T2. The majority of the patients and their families evaluated the childrens general health status as excellent or very good in both moments of the study. In general doctors evaluated their patients general health status at T1 as good or fair and very good or good at T2. Correlation of thegeneral health scores between patients and their families was high at T1, but not so high at T2. In conclusion: 1) most patients, their families and doctors reported a HRQL reduction during the initial phase of treatment, but HRQL was better later on; 2) pain was the most frequent troublesome attribute referred to in the study, but scores were significantly better from T1 to T2; 3) patients and families HRQL scores were highly correlated; 4) doctors evaluation tended to underestimate HRQL of their patients.